2019
DOI: 10.3389/fimmu.2019.01265
|View full text |Cite
|
Sign up to set email alerts
|

Roles of GM-CSF in the Pathogenesis of Autoimmune Diseases: An Update

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) was first described as a growth factor that induces the differentiation and proliferation of myeloid progenitors in the bone marrow. GM-CSF also has an important cytokine effect in chronic inflammatory diseases by stimulating the activation and migration of myeloid cells to inflammation sites, promoting survival of target cells and stimulating the renewal of effector granulocytes and macrophages. Because of these pro-cellular effects, an imbalance in GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 133 publications
(172 reference statements)
4
140
0
2
Order By: Relevance
“…GM-CSF is upstream of IL-6 and induces an inflammatory transcriptional program through JAK/ STAT signaling. 101 Inactivation of GM-CSF in CAR T on June 9, 2020 by guest. Protected by copyright.…”
Section: Interferon Gammamentioning
confidence: 99%
See 1 more Smart Citation
“…GM-CSF is upstream of IL-6 and induces an inflammatory transcriptional program through JAK/ STAT signaling. 101 Inactivation of GM-CSF in CAR T on June 9, 2020 by guest. Protected by copyright.…”
Section: Interferon Gammamentioning
confidence: 99%
“…Although the safety profiles of anti-GM-CSF antibodies have been acceptable in phase I and phase II trials, it is important to note the potential for lung toxicities and pneumonia with these agents. 101 ► Lenzilumab (Humanigen) is a human monoclonal anti-GM-CSF antibody approved for compassionate use in patients with COVID-19. A phase III trial for COVID-19 is ongoing.…”
Section: Interferon Gammamentioning
confidence: 99%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF), found endogenously as well as exogenously, is a common factor between the two autoimmune diseases. It can be produced endogenously by various cell types, for example, T cells, B cells, monocytes, macrophages, mast cells, fibroblasts, vascular endothelial cells [30]. At the same time, exogenous GM-CSF is used as a treatment to help synthesize bone marrow-derived macrophages and granulocytes [30].…”
Section: Immunological Association In the Pathogenesismentioning
confidence: 99%
“…Clinicians noted that treatment with GM‐CSF was sometimes associated with disease flare in patients with rheumatoid arthritis 36 . Subsequent research indicated that GM‐CSF is another cytokine contributing to the pathogenesis of rheumatoid arthritis, 37,38 and therefore a potentially important target for monoclonal antibodies.…”
Section: Range Of Biological Therapies For Rheumatoid Arthritismentioning
confidence: 99%